Turning peptides into bioactive nylons. (15th July 2020) - Jebors, Said; Pinese, Coline; Montheil, Titouan; Bethry, Audrey; Verquin, Simon; Plais, Louise; Moulin, Marie; Dupont, Chloé; Garric, Xavier; Mehdi, Ahmad; Martinez, Jean; Subra, Gilles
Graphical abstract: Highlights: We turn common nylon into bioactive materials. We incorporated covalently bioactive peptide sequences into the polymer backbone. We prepared polymers containing antibacterial or wound-healing peptides. The introduction of a very low amount of peptides induced significant bioactivities. Abstract: New synthetic textiles with physical and/or biological properties are increasingly used in medical applications [1, 2]. While a simple textile coating is usually carried out to obtain biological properties, covalent grafting should be considered for long-term applications. Herein, we have developed a new hybrid bioactive nylon whose synthesis involves a peptide sequence with a diacyl derivative. Numerous types of peptide-nylons were prepared by varying the molar percentage (0.1%, 1% and 10%) and orientation of the peptide in the polymer backbone. Nylons incorporating antibacterial peptides significantly inhibited S. aureus proliferation whereas nylons functionalized with cell-adhesive peptide enhanced the proliferation of L929 fibroblast. These results show that the incorporation of the peptides directly into the nylon skeleton is efficient and provides biological properties that suggest new ways of functionalizing biomedical textiles.